1983
DOI: 10.1002/pol.1983.180210802
|View full text |Cite
|
Sign up to set email alerts
|

Tests of a free‐volume model for the permeation of gas mixtures through polymer membranes. CO2‐C2H4, CO2‐C3H8, and C2H4‐C3H8 mixtures in polyethylene

Abstract: SynopsisSteady-state permeability coefficients have been measured for equimolar mixtures of C02-CzH4, C O Z -C~H~, and CzH4-C3H8, as well as for a mixture of 74.9 mol % C02 and 25.1 mol% C2H4 in polyethylene membranes. The measurements were made at 20,35, and 50°C and a t pressures of up to 28 atm. Each component of the permeating mixtures studied had the effect of increasing the permeability coefficient for the other component. Furthermore, at equal partial pressures and a t the same temperature, the componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Although it has been reported that the free-volume model satisfactorily described the behaviour of binary mixtures through polyethylene 8 and styrene-butadiene block copolymer 9 membranes, the predictions for a silicone membrane are less successful. Experimental results and predictions from the free-volume model differ significantly and the deviation increases with increasing molecular weight.…”
Section: Experimental Layout and Resultsmentioning
confidence: 91%
“…Although it has been reported that the free-volume model satisfactorily described the behaviour of binary mixtures through polyethylene 8 and styrene-butadiene block copolymer 9 membranes, the predictions for a silicone membrane are less successful. Experimental results and predictions from the free-volume model differ significantly and the deviation increases with increasing molecular weight.…”
Section: Experimental Layout and Resultsmentioning
confidence: 91%
“…They assigned the differences observed in the case of water to its hydrogen-bonding nature rather than to a failure of the model. The validity of this model (Stern et al, 1983a(Stern et al, , 1986 has been also tested for the permeation of other small molecules (Ar, SF 6 , CF 4 and C 2 H 2 F 2 until 1.5 MPa) in PE from 5°to 50°C and for binary gas mixtures (Stern et al, 1983b;Koros et al, 1981). Vrentas and Duda (1977) used another model also based on free volume, while making use of the thermodynamic theory of Flory as well as on the entanglement theory of Bueche (1962) (friction coefficient idea).…”
Section: General Considerationsmentioning
confidence: 99%
“…This technique is very useful in the field of the selective membranes, based mainly on the analysis by gas chromatography. It allows to determine the permeability coefficient of numerous polymers to binary gas mixtures, such as CH 4 -CO 2 [36][37][38][39][40].…”
Section: Reception Into a Flowing Streammentioning
confidence: 99%